Liviu Ciulei and The Last Ones: Between Personal Trauma, Psychodrama, and Collective Drama - HAȚIEGAN, Anca (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
This paper focuses on an early role in the theatrical career of the actor, director, and scenographer Liviu Ciulei (1923-2011), created on the stage of the theatre gifted to him by his father, the civil engineer Liviu Ciulley, in 1946. The role in question is Pyotr from the play The Last Ones by Russian playwright Maxim Gorky, which premiered at the Odeon Theatre in Bucharest on the 16th of March 1948. My point is that Liviu Ciulei was drawn to this play by a psychodramatic impulse, finding in it issues related to his father who, like the protagonist in Gorky’s play, had embroiled his family in a major scandal when his son was only thirteen years old. The season in which the play premiered was marked by the increasing interference of communist authorities in art, so the intense psychodramatic process through which Liviu Ciulei consciously or unconsciously worked through his early adolescent trauma intertwined with the collective drama represented by the imposition of the Soviet-enforced communist regime in Romania at the end of World War II.